Evaluation of pH, free available chlorine and tissue dissolution property of solid dosage chlorine releasing agents for root canal irrigation based on contact time – An in vitro study - S. Aishwarya; Debolina Bishayi; Vinod Rakesh Jathanna; Manuel S. Thomas; Srikant Natarajan; Suchitra Shenoy; Aradhana Marathe (Endodontology, 2025)
Aim: The aim of the study was to evaluate the pH, free available chlorine (FAC), and tissue dissolution property of various chlorine-releasing solutions prepared from predosed tablets based on the period since the preparation of the solution. Methods: Groups 1–3 are the study solutions prepared by dissolving 2.5 g of the chemical in powder form in 100 mL distilled water to obtain a 2.5% solution. The control solution is the commercially available 2.5% sodium hypochlorite (NaOCl) solution. The solutions were freshly prepared and used immediately before testing each aspect of the study. (1) Group 1: 2.5% calcium hypochlorite, (2) Group 2: 2.5% chlorine dioxide (ClO2), (3) Group 3: 2.5% sodium dichloroisocyanurate, (4) Group 4: 2.5% NaOCl, (5) Group 5: saline (negative control). Results: The comparison of pH, FAC, and tissue dissolution property between NaOCl and ClO2 was statistically nonsignificant, whereas the comparison was significant with respect to the other test solutions. Conclusion: ClO2 shows more similarity to NaOCl as an irrigant used for root canal treatments. There was not any significant difference between ClO2 and NaOCl in its FAC and tissue dissolution properties.